PERANCANGAN SISTEM INFORMASI INVENTORY BERBASIS WEB DENGAN METODE PROTOTYPE (STUDI KASUS KALAM STORE) - Hermansyah, Hermansyah; Riyandi, Albert (Jurnal Ilmu Komputer (JUIK), 2025)
This study aims to design and implement a web-based inventory information system to enhance efficiency in stock management at Kalam Store. The prototyping method was employed as the system development approach due to its capability to iteratively adapt to user needs. System testing was conducted using the User Acceptance Testing (UAT) method to evaluate system performance based on ease of use, recording accuracy, and effectiveness in supporting operations. The test results indicate that the developed system improves stock recording accuracy, reduces the risk of data loss, and accelerates the inventory reporting process. Therefore, the implementation of this web-based inventory information system can serve as an effective solution for enhancing efficiency and accuracy in stock management at Kalam Store.